2022
DOI: 10.1158/1055-9965.epi-22-0630
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Mutational Burden by Whole-Genome Sequencing in Resected NSCLC of Never Smokers

Abstract: Background: Data are scarce about tumor mutational burden (TMB) as a biomarker in never smokers with non-small-cell lung cancer (NSCLC). Methods: TMB was assessed by whole-genome sequencing (WGS) and compared with in-silico reduced whole-exome sequencing (WES) and targeted commercial NGS gene panels in 92 paired tumor-normal samples from never smokers who underwent NSCLC resection with curative intent. Analyses were performed to test for association with survival after surgery and to identify the optimal progn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…29,55 Four studies utilized the U.S. Food and Drug Agency approved gene panel tests, namely, FoundationOne, FoundationOne CDx (F1 CDx), and MSK-IMPACT, that have shown acceptable concordance with WES in empirical and in-silico TMB assessment. 18,29,31,32,56,57 Similarly, a pooled analysis from TCGA database did not find a significant prognostic impact of TMB on LUAD (HR 1.35, 95% CI 0.89, 2.05) and LSCC (HR, 0.77, 95% CI 0.50, 1.18) survival independent of TMB assessment methods (WES, MSK-IMPACT, and FoundationOne CDx). 58 Two international consortiums, the Friends of Cancer Research and Quality Assurance Initiative Pathology validated bioinformatic algorithms, standardized panelbased TMB estimates using in-silico analysis, and assessed between-TMB panel variations in FFPE tumor specimens for multiple cancer types, thereby taking TMB one step closer to a more refined prognostic biomarker.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…29,55 Four studies utilized the U.S. Food and Drug Agency approved gene panel tests, namely, FoundationOne, FoundationOne CDx (F1 CDx), and MSK-IMPACT, that have shown acceptable concordance with WES in empirical and in-silico TMB assessment. 18,29,31,32,56,57 Similarly, a pooled analysis from TCGA database did not find a significant prognostic impact of TMB on LUAD (HR 1.35, 95% CI 0.89, 2.05) and LSCC (HR, 0.77, 95% CI 0.50, 1.18) survival independent of TMB assessment methods (WES, MSK-IMPACT, and FoundationOne CDx). 58 Two international consortiums, the Friends of Cancer Research and Quality Assurance Initiative Pathology validated bioinformatic algorithms, standardized panelbased TMB estimates using in-silico analysis, and assessed between-TMB panel variations in FFPE tumor specimens for multiple cancer types, thereby taking TMB one step closer to a more refined prognostic biomarker.…”
Section: Discussionmentioning
confidence: 92%
“…Subsequently, 119 articles underwent full-text screening and 10 studies finally fulfilled the inclusion criteria. [16][17][18][19][28][29][30][31][32][33] The PRISMA flowchart for the study selection process is presented in Figure 1.…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…The TIM-3 positivity/PD-1 positivity/CD8 negativity subgroup had the worst prognosis, whereas the TIM-3 negativity/PD-1 negativity/CD8 positivity subgroup had the best forecast [ 84 ]. Regarding early-stage nonsmoking patients, tumour mutation burden (TMB) was a poor prognostic indicator for OS [ 85 ]. Conversely, another study demonstrated that TMB had no prognostic value on stage I–II resected LUAD [ 86 ].…”
Section: Resultsmentioning
confidence: 99%